Enhancement of Intracellular Calcium Ion Mobilization by Moderately but Not Highly Positive Material Surface Charges - Gruening, Martina; Neuber, Sven; Nestler, Peter; Lehnfeld, Jutta; Dubs, Manuela; Fricke, Katja; Schnabelrauch, Matthias; Helm, Christiane A.; Müller, Rainer; Staehlke, Susanne; Nebe, J. Barbara (Frontiers in Bioengineering and Biotechnology, 2020)
Electrostatic forces at the cell interface affect the nature of cell adhesion and function; but there is still limited knowledge about the impact of positive or negative surface charges on cell-material interactions in regenerative medicine. Titanium surfaces with a variety of zeta potentials between -90 mV and +50 mV were generated by functionalizing them with amino polymers, extracellular matrix proteins/ peptide motifs and polyelectrolyte multilayers. A significant enhancement of intracellular calcium mobilization was achieved on surfaces with a moderately positive (+1 to +10 mV) compared with a negative zeta potential (-90 to -3 mV). Dramatic losses of cell activity were observed on surfaces with a highly positive zeta potential (+50 mV). This systematic study indicates that cells do not prefer positive charges in general, merely moderately positive ones. The cell behavior of MG-63s could be correlated with the materials´ zeta potential; but not with water contact angle or surface free energy. Our findings present new insights and provide an essential knowledge for future applications in dental and orthopedic surgery.